Apakah Sales Growth, Leverage dan Capital Intensity Mempengaruhi Tax Avoidance? - Adriyanti Agustina Putri; Zul Azmi; Jumadil Arsa (Akuntansi & Ekonomika, 2021)
This research is important to do to examine and analyze the effect of sales growth, leverage, and capital intensity on tax avoidance. The population in this study were manufacturing companies listed on the Indonesian Stock Exchange (BEI) 2015-2019, totaling 182 companies. The sample was selected by using purposive sampling and selected 35 companies. This study uses secondary data in the form of financial reports which can be accessed through the website www.idx.co.id. The method of analysis used in this study is multiple linear regression analysis using the SPSS version 23. The results of this study can prove that sales growth, leverage, and capital intensity have an effect on tax avoidance. Increased sales growth will trigger companies to avoid paying large taxes by carrying out optimal tax planning. High leverage causes the company to pay less taxes. The higher the intensity capital, the more it can reduce the company's tax burden.